Sucrose as a stable tracer for quantifying endodontic leakage - Qiong Xu; Gary S.P. Cheung; Wen-Juan Deng; Jun-Qi Ling; Wei-Lan Li (Elsevier, 2012)
Background/purpose: Coronal or apical leakage is a major cause of endodontic treatment failure. To evaluate sucrose as a tracer for leakage testing for various filling materials involved in endodontic treatment. Materials and methods: The stability of sucrose and glucose was examined by immersing 11 common filling materials (1.5 × 3 mm blocks, cured for 1 week at 37°C in 100% relative humidity; n = 10 for each) in a 10mM solution of either sucrose or glucose. The concentration of the solution was measured after 1 week, 2 weeks, 4 weeks, and 8 weeks of immersion and compared. Then, the two tracers were used to test the sealing ability of zinc oxide-eugenol cement (IRM) and amalgam root-end fillings. Each material (n = 40 for each) was equally divided into two subgroups, these were evaluated with either glucose or sucrose as the tracer substance, and the amount of leakage was determined after 24 h, and 1 week, 2 weeks, 3 weeks, 4 weeks, 6 weeks, and 8 weeks. Results: Sucrose was stable with all materials at all time points. The concentration of glucose had significantly diminished after 1 week of immersion with mineral trioxide aggregate (MTA) or Sealapex (P < 0.001), but not with other filling materials (P > 0.05). Leakage results were similar (P > 0.05) when glucose and sucrose were used as the tracer substance, respectively. Amalgam leaked significantly less than IRM after 3 (sucrose test) and 4 weeks (glucose test) (P < 0.05). Conclusion: Sucrose appears to be stable in the presence of various endodontic materials, and can be used as a stable tracer substance for detecting endodontic microleakage.